New species of Colombian Triplocania Roesler (Psocodea: ‘Psocoptera’: Ptiloneuridae) - González-Obando, Ranulfo; Carrejo-Gironza, Nancy; Aldrete, Alfonso N. García (Zootaxa, 2017)
Based on a survey of the genus Triplocania (Psocodea: ‘Psocoptera’) in forests of natural areas and Natural Parks in Colombia, 46 species were found, 42 of which are new to science and are here described and illustrated. Added to T. colombiana García Aldrete, the number of species of Triplocania now known in Colombia is raised to 47. To date, 40 species described in this paper are recorded only in Colombia, and seven species are shared with neighboring countries, three with Brazil, one with Venezuela, two with Ecuador, and one with Ecuador and Brazil. Females of three previously known species are also described. An identification key to the species of Triplocania present in Colombia is included.